2020
DOI: 10.30878/ces.v27n1a5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de receptores GPS de bajo costo de alta sensibilidad para trabajos geodésicos. Caso de estudio: línea base geodésica

Abstract: Se evalúa una línea base geodésica mediante la implementación de antenas y receptores de bajo costo en sistemas embebidos, así como un receptor geodésico de una frecuencia. Estas mediciones fueron ligadas a una estación de referencia continua de la Red Geodésica Nacional Activa, ubicada en Culiacán, Sinaloa, con el objetivo de determinar la precisión de los equipos de bajo costo estudiados. Para ello se analizan las coordenadas y distancias obtenidas al aplicar el método de posicionamiento diferencial con soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(21 reference statements)
0
2
0
1
Order By: Relevance
“…Similarly, all observations were decimated to 15 s with TEQC software for static relative method, therefore Topcon Tools (Topcon, 2009) software was used for processing observations. Code and Phase observables were used with an elevation cut off angle of 15° (10 to 15° is commonly used as less elevation in the atmospheric effect degrade the received signal, since the visibility of the satellite is lower) (Hofmann-Wellenhof et al, 2007;Zamora-Maciel et al, 2020), precise ephemeris (SP3) from IGS (Spofford & Remondi, 1994), and IGS ANTEX file for Receiver antenna phase center correction. The obtained coordinates were analyzed using the official reference frame in Mexico (ITRF08…”
Section: Test Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, all observations were decimated to 15 s with TEQC software for static relative method, therefore Topcon Tools (Topcon, 2009) software was used for processing observations. Code and Phase observables were used with an elevation cut off angle of 15° (10 to 15° is commonly used as less elevation in the atmospheric effect degrade the received signal, since the visibility of the satellite is lower) (Hofmann-Wellenhof et al, 2007;Zamora-Maciel et al, 2020), precise ephemeris (SP3) from IGS (Spofford & Remondi, 1994), and IGS ANTEX file for Receiver antenna phase center correction. The obtained coordinates were analyzed using the official reference frame in Mexico (ITRF08…”
Section: Test Areamentioning
confidence: 99%
“…Wielgocka et al (2021) presented the feasibility of using low-cost dual-frequency GNSS receivers for land surveying, they also used a wellknown ZED-F9P receiver in conjunction with ANN-MB-00-00 antenna where the obtained results reached cm of precision in PPP with a 2.4 h of the session, regarding the vertical component the results still are inaccurate. As per the Static relative method in short and long distances, Romero-Andrade et al (2020) and Zamora-Maciel et al (2020), evaluate a geodetic baseline at ~5 and ~33 km from the CORS reference station, achieving a mm precision in consideration of survey time. present the reliability of the RTKLib (Takasu, 2013) software used in different embedded systems, also they found that the Precise Point Positioning could be considered for use in different embedded systems and achieve high precision.…”
Section: Introductionmentioning
confidence: 99%
“…Durante la época de los años 90, surgen los denominados equipos GNSS de bajo costo inicialmente para trabajos de mapeo (Tsakiri et al, 2018;Zamora-Maciel et al, 2020;Tsakiri et al, 2017), más sensibles en la recepción de señal logrando una potencia promedio de la señal recibida de -160 dB (Zhang and Schwieger, 2016) incluso con una sola frecuencia, en comparación a los equipos de orden geodésico que logran ~-128.5 dB (Zamora-Maciel et al, 2020).…”
Section: Introductionunclassified